NATIONAL TELEVISION AND RADIO CORPORATION OF THE KYRGYZ REPUBLIC - THE MAIN INFORMATION AND IDEOLOGICAL MEANS OF STATE POLICY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
During the years of independence, the National Television of Kyrgyzstan (KTRK) has played a significant role in the country’s socio-political and cultural life. This article analyzes key aspects of KTRK’s activities, with a particular focus on its role in shaping public opinion and implementing the state’s information and ideological policies. The historical stages of television development in Kyrgyzstan are examined, along with issues related to the legal regulation of KTRK’s activities, including relevant laws and normative legal acts. The study highlights KTRK’s importance as a tool for influencing public consciousness and contributing to the cultural development of society.
Keywords: sovereignty, media industry, ideology, law, laws, television, public opinion